Study of optical constants of( PMMA)doped with ( C14H14N3O6S-) - Mohmmad, J.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The Dopping effect by methyl orange ( )on optical constants [Refractive index (n), extinction coefficient(K0),real and imaginary parts of dielectric constant(Îµr &Îµi)] of poly methyl methacrylat (PMMA)  that additive to this polymer with both percentages 2% and 4% at thickness(145)Âµm have been studied. This study has been done by recording the absorption and transmission spectra in the wavelength range (200-900)nm . The results  showed that all  optical parameters are increased by increasing dopping rate except the transmission was decreased.